Requests for futile treatments: what mechanisms play a role? Results of a qualitative study among Dutch physicians - Inez de Beaufort; Rozemarijn Lidewij van Bruchem-Visser; Gert van Dijk; Francesco Mattace Raso (BMJ Open)
Objectives Overtreatment is increasingly seen as a challenge in clinical practice and can lead to unnecessary interventions, poor healthcare outcomes and increasing costs. However, little is known as to what exactly causes overtreatment. In 2015, the Royal Dutch Medical Association (RDMA) attempted to address this problem and distinguished several mechanisms that were thought to drive overtreatment. In 14 qualitative interviews among Dutch physicians, we investigated which mechanisms played a role in decision-making and whether all mechanisms were considered equally important.Design We asked physicians to present a case from personal experience, in which the patient or family requested continuing treatment against the advice of the physician.Participants Fourteen physicians from five different medical areas agreed to participate.Setting Interviews were held face-to-face at the workplace of the physician.Results Three closely related mechanisms were mentioned most frequently as drivers of overtreatment, as perceived by the physician: ‘death is not a common topic of conversation’, ‘‘never give up’ is the default attitude in our society’ and ‘patients’ culture and outlook on life influences their perception of death’. The mechanism ‘medical view taking priority’ was mentioned to be an inhibitor of overtreatment.Conclusions Of the 15 mechanisms described by the report of the Steering Committee of the RDMA, not all mechanisms were mentioned as driving overtreatment. Three mechanisms were mentioned most as being a driver of overtreatment (‘death is not a common topic of conversation’; ‘‘never give up’ is the default attitude in our society’' and ‘patients’ culture and outlook on life influences their perception of death’), some played no role at all, and others were considered to be inhibitors of overtreatment, especially the mechanism ‘medical view taking priority’.